Prognosis Prediction of Uveal Melanoma After Plaque Brachytherapy Based on Ultrasound With Machine Learning - Luo, Jingting; Chen, Yuning; Yang, Yuhang; Zhang, Kai; Liu, Yueming; Zhao, Hanqing; Dong, Li; Xu, Jie; Li, Yang; Wei, Wenbin (Frontiers in Medicine, 2022)
Abstract Introduction: Uveal melanoma (UM) is the most common intraocular malignancy in adults. Plaque brachytherapy remains the dominant eyeball-conserving therapy for UM. Tumor regression in UM after plaque brachytherapy has been reported as a valuable prognostic factor. The present study aimed to develop an accurate machine-learning model to predict the 4-year risk of metastasis and death in UM based on ocular ultrasound data. Material and Methods: A total of 454 patients with UM were enrolled in this retrospective, single-center study. All patients were followed up for at least four years after plaque brachytherapy and underwent ophthalmologic evaluations before the therapy. B-scan ultrasonography was used to measure basal diameters and thickness of tumors preoperatively and postoperatively. Random Forest (RF) algorithm was used to construct two prediction models: whether a patient will survive for more than four years and whether the tumor will develop metastasis within four years after treatment. Results: Our predictive model achieved an Area under Receiver Operating Characteristic Curve (AUC) of 0.708 for predicting death using only a one-time follow-up record. Including data from two additional follow-ups, increased the AUC of the model to 0.883. We attained AUCs of 0.730 and 0.846 with data from one and three-time follow-up, respectively, for predicting metastasis. The model found that the amount of postoperative follow-up data significantly improved death and metastasis prediction accuracy. Furthermore, we divided tumor treatment response into four patterns. The D(decrease)/S(stable) patterns are associated with a significantly better prognosis than the I(increase)/O(other) patterns. Conclusions: The present study developed a RF model to predict the risk of metastasis and death from UM within four years based on ultrasound follow-up records following plaque brachytherapy. We intend to further validate our model in prospective datasets, enabling us to implement timely and efficient treatments.